2010
DOI: 10.2215/cjn.08881209
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Hypoxemia and Periodic Limb Movement Predict Mortality in Patients on Maintenance Hemodialysis

Abstract: Background and objectives: Sleep disorders, including sleep-disordered breathing and periodic limb movements during sleep, are associated with an increased risk for cardiovascular diseases, which are the leading causes of death in patients with ESRD. This study investigated the association between sleep disorders and mortality in patients with ESRD.Design, setting, participants, & measurements: Thirty patients on maintenance hemodialysis, who were clinically stable for >2 months, underwent overnight polysomnog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 24 publications
5
31
1
1
Order By: Relevance
“…These prevalence figures are higher than most previous reports [12, 1416] Central sleep apnea was much more common in haemodialysis compared to non-dialysis participants (31% versus 7%), but CAI ≥ 30 was present in only a single patient. The reported prevalence for central sleep apnea in subjects with CKD was 0 to 75% in a recent systematic review [35].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…These prevalence figures are higher than most previous reports [12, 1416] Central sleep apnea was much more common in haemodialysis compared to non-dialysis participants (31% versus 7%), but CAI ≥ 30 was present in only a single patient. The reported prevalence for central sleep apnea in subjects with CKD was 0 to 75% in a recent systematic review [35].…”
Section: Discussioncontrasting
confidence: 59%
“…A high prevalence of sleep apnea has been recognized in patients with CKD since the 1980s with the prevalence of severe sleep apnea (AHI ≥ 30) reported to be present in 20% of those with severe non-dialysis CKD and 26% of those on hemodialysis [12]. Other studies, of varying quality, have reported a prevalence for AHI ≥ 5 in those on hemodialysis of between 50 and 83% [1316] and there is data to suggest that a lower estimated glomerular filtration rate (eGFR) is associated with more severe sleep apnea in CKD patients [17]. …”
Section: Introductionmentioning
confidence: 99%
“…310 The profound consequences of atherosclerosis induced by sleep apnea are evident by it being an independent risk factor for cardiovascular mortality both in the general population and in patients with ESRD. 76,84,[311][312][313][314][315][316] Renal Figure 1. The hypoxia cycle driving chronic kidney disease.…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%
“…Several reports in the literature are corroborating to this: risk of atrial fibrillation in patients with left ventricular systolic dysfunction [17], the snoring per si increasing the risk of heart failure and mortality [18], increasing mortality risk in patients with CKD on hemodialysis [15] and peritoneal dialysis [16] and increasing mortality risk associated with hypoxemia [19]. …”
Section: Introductionmentioning
confidence: 75%